MENGENALI PATOGENESIS DAN PENYEBARAN SKABIES DI DAERAH BERIKLIM TROPIS DAN SUBTROPIS - Vanneetha Arivananthan (Intisari Sains Medis, 2016)
Introduction: scabies has spread throughout the world , especially in the tropics and subtropical. Scabies is a skin disease are often found in indonesia. This disease it was easy contagious and a lot of factors help their spreading. In Indonesia, incident this disease is not a definite number , but based on health department report, scabies ranked 3rd than 10 of the largest the skin diseases in Pelita IV. Transmission through direct contact (skin contact) and may also indirectly (through things). Patient symptoms is the itchy feeling especially at night (pruritus nocturnal) or during hot weather and when patients sweating.Cases: Patients men, age 11, Balinese ethnic, religious Hindu come on april 22nd 2014 with complaints spots show up on the sidelines of the fingers, the back of the hand, palms, lower abdominal and that part of the penis that feels itchy especially at night. This symptoms have been felt since 1 month ago. There is no food and drug allergic history in patient and family.